Characterization of Efficiency and Mechanisms of Cold Atmospheric Pressure Plasma Decontamination of Seeds for Sprout Production - Waskow, Alexandra; Betschart, Julian; Butscher, Denis; Oberbossel, Gina; Klöti, Denise; Büttner-Mainik, Annette; Adamcik, Jozef; von Rohr, Philipp Rudolf; Schuppler, Markus (Frontiers in Microbiology, 2018)
The consumption of fresh fruit and vegetable products has strongly increased during the past few decades. However, inherent to all minimally processed products is the short shelf life, and the risk of foodborne diseases, which have been increasingly related to such products in many parts of the world. Because of the favorable conditions for the growth of bacteria during the germination of seeds, sprouts are a frequent source for pathogenic bacteria, thus highlighting the need for seed decontamination to reduce the risk of foodborne illness. Consequently, this study focused on cold atmospheric pressure plasma treatment of artificially inoculated seeds in a diffuse coplanar surface barrier discharge to determine the inactivation efficiency for relevant foodborne pathogens and fungal spores. Plasma treatment of seeds resulted in a highly efficient reduction of microorganisms on the seed surface, while preserving the germination properties of seeds, at least for moderate treatment times. To better characterize the mechanisms that contribute to microbial inactivation during plasma treatment, an experimental setup was used that facilitated the separate investigation of UV and other plasma components. The combination of life/dead staining methods with confocal laser scanning microscopy analysis revealed a less efficient inactivation of bacteria by ozone and other reactive species generated during plasma treatment compared to UV. Further characterization of the effect of cold atmospheric pressure plasma on bacterial cells was performed by atomic force microscopy imaging of identical E. coli cells before and after treatment. The impact of plasma treatment on bacterial cells was demonstrated by an increase in surface roughness and visible indentations on the bacterial cell surface that suggest a physical damage of the cell envelope. In conclusion, cold atmospheric pressure plasma shows potential for being a relevant decontamination technology in the production process of sprouts, which may contribute to food safety and prolonged shelf life of the product.